Affective Switch Associated With Oral, Low Dose Ketamine Treatment in a Patient With Treatment Resistant Bipolar I Depression. Case Report and Literature Review - Wilkowska, Alina; Szałach, Łukasz; Słupski, Jakub; Wielewicka, Aleksandra; Czarnota, Małgorzata; Gałuszko-Węgielnik, Maria; Wiglusz, Mariusz S.; Cubała, Wiesław J. (Frontiers in Psychiatry, 2020)
There is a growing evidence for the rapid and robust anti-depressive effect of ketamine in unipolar and bipolar treatment resistant depression although evidence for the risk of affective switch is still limited. This case presents bipolar I disorder patient with treatment resistant depressive episode experiencing a switch to manic episode with mixed features shortly after receiving 8 subanaesthetic doses of oral ketamine as an add-on treatment preceded by two-day period of manic symptoms.